Dicefalia em bovino: relato de caso - Bertoli, Giuliana [UNESP]; Mendes, Juliana Pedroso [UNESP]; Filadelpho, André Luis [UNESP]; Guazzelli Filho, Joffre [UNESP]; Silva, José Ricardo de Carvalho Pinto e [UNESP]; Schimming, Bruno Cesar [UNESP]; Peres, Jayme Augusto; Barcelos, Rodrigo Patera (My University, 2014)
The dicefalia is a rare congenital anomaly malformation. It is characterized by duplication and total separation of face, cranium and brain structures forming two heads in a single individual. This anomaly occurs in different species of anaimals, being most frequently affected cattle. goats, cats and man.

A dicefalia é uma anomalia rara de malformação e tem origem congênita. Caracteriza-se pela duplicação e separação total das estruturas faciais, craniais e do encéfalo, formando duas cabeças em um único indivíduo. Essa anomalia ocorre em diferentes espécies de animais, sendo mais frequentemente afetados os bovinos, caprinos, felinos e o homem.
Dicefalia in bovine: case report
Keywords: Dicefalia; Anomaly; Malformation; Dicefalia; Anomalia; Malformação